Metformin Reduced Collagen Deposition and Contractility, but Increased Collagen Degradation in in vitro Posterior Capsule Opacification Model - Frisma Sagara Brilliyanto; Gatut Suhendro; Indri Wahyuni; Maftucah Rochmanti; Windhu Pramono (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Posterior capsule opacification (PCO) often occurs after cataract surgery. Metformin has been known to have an ability to inhibit fibrosis. This study aimed to investigate the effects of metformin on cell contractility, collagen deposition and degradation in human lens epithelial cells (HLEC) of cataract patients.METHODS: HLEC were isolated from the anterior lens capsule of patients undergoing cataract surgery. The HLEC culture was carried out using explant culture technique. The in vitro PCO model was created by scratching technique on HLEC cultures. The treatment groups were given 0.1, 0.5 and 1 mM metformin, respectively, while the control group were given 10% fetal bovine serum (FBS). On the 7th day after scratching technique, the collagen deposition, collagen degradation and cell contractility were evaluated.RESULTS: Collagen deposition in HLEC was significantly reduced after given 0.1 mM, 0.5 mM and 1 mM metformin (17.92±6.16 mg/mL, 12.92±4.31 mg/mL, 11.25±5.30 mg/mL, respectively), compared to the control group (31.46±7.52 μg/mL, p=0.002). Collagen degradation significantly was increased in the 0.1 mM, 0.5 mM and 1 mM metformin groups (4.77±9.27 mg/mL, 6.59±1.16 mg/mL, 6.35±1.90 mg/mL, respectively) compared to the control group (2.21±2.78 μg/mL, p=0.002). While, collagen contractility in HLEC was significantly reduced in 0.1mM, 0.5mM and 1 mM metformin groups (16.39±3.89%, 13.89±2.59%, 11.93±2.44%, respectively), compared to the control group (44.25±4.95%, p=0.000).CONCLUSION: Metformin reduced collagen deposition and contractility, but increased collagen degradation in HLEC of cataract patients through mechanism of extracellular matrix remodeling.KEYWORDS: metformin, human lens epithelial cell, fibrosis